(untitled) (Global Journal of Computer Science and Technology, 2023)
Collective intelligence CI is critical for groups to solve a variety of problems Such emergent property of the group as a whole is the result of group interaction processes that may inevitably lead to different cognition collaboration and relationship between individuals even conflict within group A key question concerning problem solving is whether and how conflict influences the emergency of collective intelligence Here we used trust and distrust to indicate harmony and conflict state of the group We utilized agent-based modeling to examine the emergent outcomes resulting from trust-based group interaction Our results support the conclusion that CI emerges in moderate task complexity conditions We further showed that the maximum level of CI is predicted by distrust We also found that trust-based positive and negative feedback mechanism worked simultaneously in group problem solving process And these two mechanisms played the role of valve controlling knowledge flow and bridge connecting individuals respectively which can better explain how trust influences the emergence of CI Finally we found that appropriate conflict is beneficial to collective intelligence